2003
DOI: 10.2739/kurumemedj.50.91
|View full text |Cite
|
Sign up to set email alerts
|

Association between Diabetes Mellitus and Hepatocellular Carcinoma: Results of a Hospital- and Community-based Case-control Study

Abstract: The present study was performed to investigate the relationship between diabetes mellitus (DM) and primary hepatocellular carcinoma (HCC). Incident HCC cases were recruited in Kyushu, Japan. Ethnicity-, age-, gender-, residence-matched hospital controls and community controls were collected. Information on viral hepatitis B (HB5Ag) or viral hepatitis C infection, history of blood transfusion, past histories including DM, amount of drinking or smoking, and genotypes of alcohol metabolizing enzymes was collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 19 publications
1
22
0
1
Order By: Relevance
“…Of the 102 possibly eligible studies after the initial screening, the full text search that ensued resulted in removal of 21 studies. Hence, 81 studies were included in the systematic review . Seventy‐two studies assessed the association between smoking and risk of development of HCC and nine studies assessed the association between smoking and the risk of mortality in HCC patients.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 102 possibly eligible studies after the initial screening, the full text search that ensued resulted in removal of 21 studies. Hence, 81 studies were included in the systematic review . Seventy‐two studies assessed the association between smoking and risk of development of HCC and nine studies assessed the association between smoking and the risk of mortality in HCC patients.…”
Section: Resultsmentioning
confidence: 99%
“…These data raise concerns that the prevalence of occult HBV may be more common among type 2 diabetes mellitus (DM) patients because of the abnormalities of the immune system. Additionally, increased HCC prevalence in diabetic population has been reported and the associated steatohepatitis has been suggested as a causative factor [10,11]. It is plausible that the increased occult HBV prevalence among DM patients may imply a possible direct or an additive role with steatohepatitis in the development of HCC.…”
Section: Introductionmentioning
confidence: 97%
“…It is unknown whether the patient was a heavy alcohol drinker, although autopsy findings showed liver cirrhosis. The present case did not show steatohepatitis, while the previous studies suggested that a past history of diabetes mellitus might be a risk factor for hepatitis, cirrhosis and HCC, and the earlier patients were negative for all serological markers of hepatitis B and C virus infection (15)(16)(17). From these considerations, it is surmised that the HCC in the present case probably progressed from diabetes through hepatitis and cirrhosis.…”
Section: Discussionmentioning
confidence: 45%